A criticism on the UNSC veto power and the introduction of majority rule as an alternative / Mohamad Syazwan Shah Mohamad Ali, Megat Mahathir Megat Tharih Afendi and Noor Azizi Abdul Aziz - Mohamad Ali, Mohamad Syazwan Shah; Megat Tharih Afendi, Megat Mahathir; Abdul Aziz, Noor Azizi (2012)
This project in its present form is the result of a review conducted on the Veto Power of the United Nations Security Council (the UNSC). The purpose for this project was to review the Veto Power of the Security Council and highlight its defect before highlighting the advantages of the concept of Majority Rule that should be implemented in the Security Council. The Veto Power of UNSC was reviewed by means of a qualitative research, library research and semi-structured interviews with two lecturers who are also experts on the area of the international law and the United Nations (the UN). This study was conducted within the UNSC, particularly in relation to the powers delegated towards the five permanent members (The P5) of the Security Council. Since the establishment of the Security Council, the P5 have used their power of Veto in accordance only towards their national interests. The reasoning behind the use of that power had strayed from the initial reason for which it was included in the UN Charter, which was to prevent the UN from taking direct action against any of its principal founding members. The contributions of this project are twofold. First, a common subsidiary argument concerns the practical difficulty of bringing agreement among the P5 to abolish their prerogative power. Secondly, the propositions that carefully analyses to replace the veto power with majority rule.